The tadpole of Hylodes meridionalis (Mertens, 1927), a lotic stream anura from the Atlantic Rainforest of Brazil - Nogueira-Costa, Paulo; Wachlevski, Milena (Zootaxa, 2015)
The genus Hylodes Fitzinger, 1826, comprises 25 species (Sá et al. 2015), of small to medium-sized diurnal frogs, that habit lotic stream habitats of the Atlantic Rainforest domain. Only 17 species of Hylodes genus had its larvae described so far (Costa et al. 2010; Sá et al. 2015). Regarding the osteology, only one species has its chondrocranium described (Bilate et al. 2012). Herein we describe the tadpole of H. meridionalis and its osteology.